Membership has its privileges: The effect of membership in international organizations on FDI - Axel Dreher; Heiner Mikosch; Stefan Voigt (Center for Economic Studies and ifo Institute (CESifo), 2010)
We argue that membership in International Organizations (IOs) is an important determinant of FDI inflows. To the extent that membership restricts a country from pursuing policies that are harmful to investors, it can signal low political risk. Using data over the 1971-2005 period, we find that membership in IOs does indeed increase inflows of FDI. Controlling for the endogeneity of membership, we find this effect to be substantively important and robust to the method of estimation.
Keywords: F02; F21; H11; K33; P26; 330; membership in international organizations; FDI; investment climate; political risk; signaling; separating equilibrium; Internationale Organisation; Mitgliedschaft; Standortfaktor; Ökonomische Sicherheit; Signalling; Schätzung; Welt